The AKTIFITAS LARVASIDAL MINYAK CHROMOLAENA ODORATA TERHADAP LARVA LALAT RUMAH - Yuliani, Ni Sri (Prodi Pendidikan Biologi FKIP Universitas Kristen Artha Wacana, 2024)
Larvae, also called maggots, are part of the metamorphic form of house flies which are often found in livestock waste. If not handled properly it can increase the adult fly population. Medicinal plants such as C. odorata, which are known as weeds, are known to have active antiparasitic compounds which are used to control flies or their larval forms naturally. The aim was to study the larvicidal activity of C. odorata oil against house fly larvae. The method used in this research was a completely randomized design with four treatments and five replications. 20 third instar larvae were tested per treatment replication, for a total of 400 individuals. The oil extract treatment was divided into 3 different concentrations, namely 5%, 10%, 15% and a 10% soap solution control as a comparison. The extract and soap solution are applied by spraying directly onto the larvae. The variable measured was larval death 36 hours after spraying the extract. The data obtained were analyzed descriptively by calculating the percentage of mortality. The research results showed that mortality rates from the oil extract were 4%, 18% and 11%, while the control was 88%. Based on these results, it can be seen that C. odorata oil has larvicidal activity with the best concentration of 10%.